'Leukodystrophy‐like' phenotype in children with myelin oligodendrocyte glycoprotein antibody‐associated disease. (30th December 2017) - Hacohen, Yael; Rossor, Thomas; Mankad, Kshitij; Chong, Wk 'Kling'; Lux, Andrew; Wassmer, Evangeline; Lim, Ming; Barkhof, Frederik; Ciccarelli, Olga; Hemingway, Cheryl
Abstract : Aim: To review the demographics and clinical and paraclinical parameters of children with myelin oligodendrocyte glycoprotein (MOG) antibody‐associated relapsing disease. Method: In this UK‐based, multicentre study, 31 children with MOG antibody‐associated relapsing disease were studied retrospectively. Results: Of the 31 children studied, 14 presented with acute disseminated encephalomyelitis (ADEM); they were younger (mean 4.1y) than the remainder (mean 8.5y) who presented with optic neuritis and/or transverse myelitis ( p <0.001). Similarly, children who had an abnormal brain magnetic resonance imaging (MRI) at onset ( n =20) were younger than patients with normal MRI at onset ( p =0.001) or at follow‐up ( p <0.001). 'Leukodystrophy‐like' MRI patterns of confluent largely symmetrical lesions was seen during the course of the disease in 7 out of 14 children with a diagnosis of ADEM, and was only seen in children younger than 7 years of age. Their disability after a 3‐year follow‐up was mild to moderate, and most patients continued to relapse, despite disease‐modifying treatments. Interpretation: MOG antibody should be tested in children presenting with relapsing neurological disorders associated with confluent, bilateral white matter changes, and distinct enhancement pattern. Children with MOG antibody‐associated disease present with age‐related differences in phenotypes, with a severe leukoencephalopathy phenotype in the very young and normal intracranial MRI in the older children. This finding suggests a susceptibility of the very young and myelinating brain to MOG antibody‐mediated mechanisms of damage. What this paper adds: Myelin oligodendrocyte glycoprotein (MOG) antibody‐associated demyelination manifest with an age‐related phenotype. Children with MOG antibody and 'leukodystrophy‐like' imaging patterns tend to have poor response to second‐line immunotherapy. What this paper adds: Myelin oligodendrocyte glycoprotein (MOG) antibody‐associated demyelination manifest with an age‐related phenotype. Children with MOG antibody and 'leukodystrophy‐like' imaging patterns tend to have poor response to second‐line immunotherapy. This article is commented on by Kuroda and Fujihara on pages339–340 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.